(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The background in this study is the influence of the Islamic religious education learning model in increasing learning activity in class VIII SMP Muhammadiyah Parepare which is based on Law No. 12 of 2012 and Qs Al-Alaq/96:1-5 as well as field facts that occur. The type of research used is quantitative research which is located at SMP Muhammadiyah Parepare. The data sources used are primary data and secondary data. The population is 61 students and the sample is 22 students. The data collection techniques used were observation, interviews, questionnaires and documentation. Data analysis techniques used are validation and reliability tests, descriptive analysis, data requirements test and hypothesis testing. Research results that have been obtained by research based on data analysis, namely. 1) The Islamic Religious Education learning model has an average total score of 75.6061, this indicates that Islamic Religious Education learning is in the medium category. 2) Student activeness has an average score70.9470this shows Student Active Learning is in the categorycurrently.3) there is a relationship between the learning model of Islamic religious education on student learning activeness in class VIII SMP Muahammadiya Parepare as evidenced by hypothesis testing with a significance value of 0.001 <0.05, with a determinant efficiency of 0.541% which indicates that Ho is accepted.